Epidemiology and clinical features of emergency department patients with suspected and confirmed COVID‐19: A multisite report from the COVID‐19 Emergency Department Quality Improvement Project for July 2020 (COVED‐3). (19th October 2020) - O'Reilly, Gerard M; Mitchell, Rob D; Mitra, Biswadev; Akhlaghi, Hamed; Tran, Viet; Furyk, Jeremy S; Buntine, Paul; Bannon‐Murphy, Holly; Amos, Timothy; Udaya Kumar, Maushmi; Perkins, Emma; Prentice, Alexandra; et al.
Abstract: Objective: The aim of the present study was to describe the epidemiology and clinical features of patients presenting to the ED with suspected and confirmed COVID‐19. Methods: The COVID‐19 ED (COVED) Project is an ongoing prospective cohort study in Australian EDs. This analysis presents data from eight sites across Victoria and Tasmania for July 2020 (during Australia's 'second wave'). All adult patients who met criteria for 'suspected COVID‐19' and underwent testing for SARS‐CoV‐2 in the ED were eligible for inclusion. Study outcomes included a positive SARS‐CoV‐2 test result and mechanical ventilation. Results: In the period 1 July to 31 July 2020, there were 30 378 presentations to the participating EDs and 2917 (9.6%; 95% confidence interval 9.3–9.9) underwent testing for SARS‐CoV‐2. Of these, 50 (2%) patients returned a positive result. Among positive cases, two (4%) received mechanical ventilation during their hospital admission compared to 45 (2%) of the SARS‐CoV‐2 negative patients (odds ratio 1.7, 95% confidence interval 0.4–7.3; P = 0.47). Two (4%) SARS‐CoV‐2 positive patients died in hospital compared to 46 (2%) of the SARS‐CoV‐2 negative patients (odds ratio 1.7, 95% confidence interval 0.4–7.1; P = 0.49). Strong clinical predictors of a positive SARS‐CoV‐2 result included self‐reported fever, non‐smoking status, bilateral infiltrates on chest X‐ray and absence of a leucocytosis on first ED blood tests ( P < 0.05). Conclusion: In this prospective multi‐site study from July 2020, a substantial proportion of ED patients required SARS‐CoV‐2 testing, isolation and enhanced infection prevention and control precautions. Presence of SARS‐CoV‐2 on nasopharyngeal swab was not associated with death or mechanical ventilation. Abstract : A substantial proportion of patients presenting to Australian EDs in July 2020 underwent SARS‐CoV‐2 testing and required enhanced infection prevention and control precautions. Only a small proportion returned a positive result. The presence of SARS‐CoV‐2 on nasopharyngeal testing was not associated with mechanical ventilation or death in hospital.